Placental abruption - Castilla, Fernando (2015)
OBJECTIVE: To determine maternal and perinatal morbidity and mortality caused by abruptio placentae at the Obstetrical Service, Dos de Mayo Hospital, during years 1990 through 1995. DESIGN: Descriptive study, reviewing maternal clinical histories and neonatology registry. RESULTS: During this period 133 cases of abruptio placentae ocurred, incidence 0,77%; 68 histories were found. Most frequent age varied from 20 to 30 years (57,2%), almost 50% were term pregnancies, most did not have pre natal control ot it was insufficient (70,5%), parity was less than two (63,1%). Most frequent concomitant pathology was hypertensive disease (41,1%). Major symptomatology consisted in hemorrhage (64,7%), perinatal mortality was about 50%, with severe asphyxia in most of newborns. Neonatal morbidity consisted in infections, with sepsis in 12,1%. There was no maternal mortality. Puerperal morbidity was due to preeclampsia-eclampsia (16,1%) and fever (13,2%). CONCLUSION: -Perinatal mortality is high, infections are important cause of neonatal and puerperal morbidity in abruptio placentae.